Factors affecting marketing channel choice decisions in citrus supply chain : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Agribusiness at Massey University, Palmerston North, New Zealand - Siddique, Muhammad Imran (Massey University, 2015)
Fruits and vegetables are seasonal and perishable in nature and require efficient and effective marketing practices. Therefore, fruit and vegetable marketing channel choice decisions, being a part of efficient marketing practices, require more attention. In agribusiness, particularly for fruit and vegetables, the presence of a large number of intermediaries and the availability of different marketing channels make decision making more complex. The agricultural marketing system in Pakistan, particularly for fruit and vegetables, is very diverse. Nearly all citrus marketing channels are dominated by citrus growers, pre-harvest contractors and exporters of citrus fruit in the Pakistan’s citrus supply chain. Along with price, a number of factors play a key role in the selection of a particular marketing channel for fruit and vegetables. This study aims to identify and evaluate the major factors affecting marketing channel choice decisions of citrus growers and pre-harvest contractors in Pakistan’s citrus supply chain. Using qualitative and quantitative techniques, this study took into account the various transaction costs, socioeconomic, demographic and psychological factors in citrus growers marketing channel choice selection and measured the actual impact of each factor on the overall decision. Along with citrus growers, factors affecting marketing channel choice decisions of pre-harvest contractors were also analysed using a multivariate technique of decision analysis i.e., conjoint analysis. Using a survey strategy and a convenient sampling technique, face to face interviews were conducted for the collection of data from citrus growers and contractors from Pakistan citrus supply chain. It was concluded that all the three groups of citrus growers placed different preference and different utility values for the different factors when made selection out of the bundle of factors. Likewise, the percentage preference and utility values between any two factors is different for all the three groups of citrus growers, although, they had the same order of preferences for the same set of factors in order to make a certain marketing channel choice decision. The results also revealed that all the three groups of pre-harvest citrus contractors displayed diversity in preferences and different utility values for the different factors when made selection out of the bundle of factors in citrus marketing decision making. In addition, the percentage preference and utility values between any two factors is different for all the three groups of citrus pre-harvest contractors. Contrary to the citrus growers, pre-harvest contractors placed different order of preference for the same set of factors in order to make a certain marketing channel choice decision. Apart from contributing into the body of literature on citrus industry of Pakistan this study also magnified the priority areas for future research and useful guidelines.
Keywords: Citrus fruit industry, Pakistan; Citrus fruit marketing; Fruit marketing